2018
DOI: 10.3791/56833
|View full text |Cite
|
Sign up to set email alerts
|

Total Internal Reflection Absorption Spectroscopy (TIRAS) for the Detection of Solvated Electrons at a Plasma-liquid Interface

Abstract: The total internal reflection absorption spectroscopy (TIRAS) method presented in this article uses an inexpensive diode laser to detect solvated electrons produced by a low-temperature plasma in contact with an aqueous solution. Solvated electrons are powerful reducing agents, and it has been postulated that they play an important role in the interfacial chemistry between a gaseous plasma or discharge and a conductive liquid. However, due to the high local concentrations of reactive species at the interface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…6 More recently, it was argued that in the plasma cathode configuration, electrons from the plasma must be injected into the liquid in order for current to be maintained, 7 and this was ultimately confirmed by optically detecting plasma-injected solvated electrons via absorption spectroscopy. 8,9 Notably, it was found that plasma-injected solvated electrons have essentially the same properties as those produced by radiolysis, such as the rate constants for various reactions reported in the radiation chemistry literature. 10,11 Solvated electrons (e − aq ), commonly called hydrated electrons when in aqueous solutions, are one of the most powerful reductants with a reduction potential of −2.88 V vs. NHE, 12 and can be used to reduce a wide variety of species.…”
mentioning
confidence: 91%
“…6 More recently, it was argued that in the plasma cathode configuration, electrons from the plasma must be injected into the liquid in order for current to be maintained, 7 and this was ultimately confirmed by optically detecting plasma-injected solvated electrons via absorption spectroscopy. 8,9 Notably, it was found that plasma-injected solvated electrons have essentially the same properties as those produced by radiolysis, such as the rate constants for various reactions reported in the radiation chemistry literature. 10,11 Solvated electrons (e − aq ), commonly called hydrated electrons when in aqueous solutions, are one of the most powerful reductants with a reduction potential of −2.88 V vs. NHE, 12 and can be used to reduce a wide variety of species.…”
mentioning
confidence: 91%
“…In a conventional evanescent wave experiment, the first medium (TIR substrate) is generally taken as a glass (e.g. silica, SiO 2 ), although such measurements can also be performed at the interface between two liquids [15], a plasma and a liquid [16] or a liquid and a gas [17]. Evanescent wave excitation of the object is possible while the refractive index, n, of the sample does not exceed that of the glass (n = 1.47 at 400 nm for silica [18]).…”
Section: Introductionmentioning
confidence: 99%
“…Solvated electrons in plasma electrochemical systems were first directly detected using a reflection-based absorption measurement now termed total internal reflection absorption spectroscopy (TIRAS) [3,13], and a basic reaction model was used to estimate their penetration depth to be l = 12.3 ± 4.9 nm [3]. (Note that is larger than the value of l = 2.5 ± 1.0 nm in the original publication of [3], but was corrected in a corrigendum due to an error in the analysis.)…”
mentioning
confidence: 99%
“…In this letter, we extend the scaling theory in equation (3) to develop a predicted scaling for the TIRAS signal with current density and experimentally confirm this predicted scaling, from which we can draw additional insight into the reaction and penetration of e -(aq) . TIRAS, illustrated in figure 1, uses differential absorption spectroscopy to detect solvated electrons at the plasma-liquid interface [13]. A negative polarity, DC glow discharge is generated between a hollow, sharp-tipped steel electrode (cathode) and the surface of a liquid electrolyte in a glass experimental cell flushed with an argon (Ar) atmosphere.…”
mentioning
confidence: 99%
See 1 more Smart Citation